Using Clips from English Television Shows in English Lessons to Improve Students’ Speaking Skills - Seni, Bungkoboy H.; Baa, Sultan; Korompot, Chairil Anwar (Journal of Excellence in English Language Education, 2025)
This article aimed to improve students’ speaking skills using clips from English television shows for year 11 students majoring in accounting at SMKN 7 Takalar. The research question is: Can the use of clips from English television shows in English lessons improve students’ speaking skills? The objective of this research was to find out whether the use of clips from English television shows in English lessons can improve students’ speaking skills. The researcher utilized a pre-experimental research design, specifically the one-group pretest-posttest research design. The population of the study was year eleven students majoring in accounting at SMKN 7 Takalar. Random sampling was done, and the research sample was class AK 1, which consisted of 20 students. The data from the pre-test and post-test were collected and analysed with SPSS 29.0. The statistics show that there was a significant difference between the pre-test and post-test, which proves the point. The mean of pre-test score was 5.12, whereas the post-test was 6.06. At the level of significance of 5%, the value of t0 (tcount) = 10.105, and the value of tt (ttable) = 2.093 with degree of freedom (df) = 19. The result was t0 (tcount) was higher than tt (ttable). Based on the findings and discussions, this research concluded that using clips from English television shows improves students’ speaking skills.